2015
DOI: 10.1002/jso.24067
|View full text |Cite
|
Sign up to set email alerts
|

Which is a more reliable indicator of survival after gastric cancer surgery: Postoperative complication occurrence or C‐reactive protein elevation?

Abstract: CRP elevation is a more reliable indicator of survival after gastric cancer surgery than postoperative complication occurrence. Surgeons should minimize the postoperative inflammatory response to improve prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 51 publications
7
75
0
1
Order By: Relevance
“…However, some studies have found that postoperative complications do not always have a negative impact on prognosis 40, 41, 42. Migita et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have found that postoperative complications do not always have a negative impact on prognosis 40, 41, 42. Migita et al .…”
Section: Resultsmentioning
confidence: 99%
“…Presently, these speculations have not been confirmed. Saito et al 42. suggested that the actual event that affects patient survival might not be postoperative complications, but excessive inflammation after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery provides the only possibility of cure in patients with gastric cancer. Despite improvements in perioperative care and surgical procedures, postoperative complications remain a major impediment and threat to survival after gastric cancer surgery[1-3]. Therefore, it is crucial to specify a reliable and simple risk assessment index to indicate the possibility of postoperative complications, and the likelihood of early and safe patient discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also reported that patients receiving perioperative blood transfusions have significantly worse postoperative outcomes in pancreatic cancer patients and that the surgical stress, which is increased by prolonged operative times, correlates with the cancer prognosis, suggesting potential prognostic impacts of the early ligation [6][7][8][9] . To enjoy the clinical usefulness of early ligation, it is necessary that IPDA, one of the major afferent arteries, be identified during PD.…”
Section: Discussionmentioning
confidence: 99%